(untitled) (Research, Society and Development, 2023)
Between negative externalities resulting from hegemonic attitudes of development and the movements that contemporary science and technologies face, it is time of reconstruction, not by the disciplinary cut out but by interdisciplinarity due to the complexity of these problems. In this context, this discussion aims to present procedures adopted to lead the participation of social actors in the elaboration of a methodology with multidimensional indicators. Thus, the challenge of adapting the axles of the culture circuit method was visualized in the economic, social, environmental and institutional dimensions supported by the pillars of sustainable development compounding on the objectives of sustainable development, enabling the culture of the social actors participating in the research, in relation to the dimensions mentioned above. The result of the adaptation was the basis for the elaboration of workshops and interviews with social actors, at first the public managers, to raise variables for the construction of a multidimensional methodology capable of planning the municipality strategies that accelerate sustainable rural development through the Municipal Plan for Sustainable Rural Development. The results showed variables loaded with meanings departing from the experiences of public managers in identifying the demands, by which they were interrelated with the dimensions: economic, social, environmental and institutional and the Sustainable Development Goals.